What Scientists Who Study Emotion Agree About. (January 2016) - Ekman, Paul
In recent years, the field of emotion has grown enormously—recently, nearly 250 scientists were identified who are studying emotion. In this article, I report a survey of the field, which revealed high agreement about the evidence regarding the nature of emotion, supporting some of both Darwin's and Wundt's 19th century proposals. Topics where disagreements remain were also exposed.